Effect of Fat Type and Calcium Level Supplementary on Growth Performance, Fat Digestibility, and Ca and P Absorption and Balance in Growing-Finishing Pigs - Jamlong Mitchaothai; Chalermpon Yuangklang; Suntorn Wittayakun; Krisit Vasupen; Sasiphan Wongsuthavas; Paiwan Srinanuan; Anton C. Beynen (Agriculture and Natural Resources, 2006)
The study was carried out to investigate the effect of two different fat types (beef tallow and sunflower oil) and level of dietary calcium (high and low) on growth performance, nutrient digestibility, calcium – phosphorus absorption and balance in growing-finishing pigs. Four castrated male pigs were designed in 4 × 4 Latin square with two weeks a period. The results showed that the supplementation of calcium tended to increase the apparent fat digestibility and increased significantly (p<0.05) the absorption and balance of calcium, but it was no influence on absorption and balance of phosphorus. It could be concluded that supplementation of vegetable oil with calcium at low level (minimal requirements) are suitable and adequate, respectively, for growing-finishing pigs.